Overlap PCR strategy and cloning of Prostate Specific Membrane Antigen (PSMA) gene in pichia pastoris yeast recombinant expression system / Nassrin Abduljalil Badroon - Abduljalil Badroon, Nassrin (2013)
In this study, PSMA was divided into 3 fragments, G1, G2 and G3. Two-step PCR was done to constructed G1 sub-divided fragments (a, b, c, d, e, and f). G2 and G3 were amplified using specific primers and the obtained PCR products were subsequently purified and proceed for cloning. In order to clone each PSMA fragment, each PCR amplified fragment were ligated into pGEM-T vector and transformed into JM109 competent cells, which provided the complete sequences of G2 and G3; with some minimum mutations in G1.Overlapping extension PCR was conducted to combine the fragments; so the G1 fragment was amplified from the isolated plasmid and G2-3 overlapped fragment was amplified using the plasmid isolated sample. PCR optimization was carried out after overlapping of G1 and G2-3, and the fragments were purified. Overlapping of PSMA G1 with G2-3 was carried out and a faint band was produced. The purified product was subsequently cloned using pGEM®-T vector; the recombinant construct was isolated by plasmid isolation and then digested with restriction enzymes such as Sfi1 and Not1. It was then purified and ligated into expression vector pPICZαA, which had been predigested with sfiI and NotI. Later on, it was transformed into Top10 competent cells. This recombinant construct (pPICZαAPSMA) was isolated and linearized with restriction enzyme Sac1.